2008
DOI: 10.1080/07357900701638459
|View full text |Cite
|
Sign up to set email alerts
|

p53 Arg72Pro Polymorphism Predicts Survival Outcome in Lung Cancer Patients in Indian Population

Abstract: In response to many forms of cellular stress, including DNA damage, the p53 protein functions to induce growth arrest, DNA repair, or apoptosis. Common allele variants in the TP53 gene modulate pathways of lung carcinogenesis and susceptibility to or prognosis of lung cancer. The prognostic role of the polymorphism was assessed in 422 subjects using PCR-RFLP. Logistic regression analysis showed a dominant presentation of Pro/Pro homozygotes in lung carcinoma population than in control population (OR = 2.1, P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
1
23
0
3
Order By: Relevance
“…The Arg/Pro polymorphism at codon 72 is one of the ten polymorphisms that have been detected in human p53 so far (30). Sreeja et al (31) have shown that the Pro allele at codon 72 may alter the enzyme activity of p53. The Pro allele seems to favour p53 binding to p73, a p53 homologue and transcription factor of some p53 target genes, which may lead to alterations in the activation of some p53-interacting genes (32).…”
Section: Discussionmentioning
confidence: 99%
“…The Arg/Pro polymorphism at codon 72 is one of the ten polymorphisms that have been detected in human p53 so far (30). Sreeja et al (31) have shown that the Pro allele at codon 72 may alter the enzyme activity of p53. The Pro allele seems to favour p53 binding to p73, a p53 homologue and transcription factor of some p53 target genes, which may lead to alterations in the activation of some p53-interacting genes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies of lung cancer have led to the discovery of hundreds of associated genes, such as those encoding p53, BRCA1, and serine/threonine kinase (Reguart et al, 2008;Sreeja et al, 2008;Strazisar et al, 2009), which can partly explain the genetic risk factors. Several lung cancer susceptibility loci have recently been identified in genome-wide association studies (Easton and Eeles, 2008; Thomas et al, 2008;Boezen, 2009;Caporaso et al, 2009;Landi et al, 2009;Chung et al, 2010;Hsiung et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genetic studies, in particular genome-wide association studies (GWAS), have led to the discovery of several chromosomal regions that contain genes associated with lung cancer risk, including those encoding p53, BRCA1, and serine/threonine kinase (Reguart et al, 2008;Sreeja et al, 2008;Strazisar et al, 2009). In addition, 5p15.33 was recently identified as a susceptibility region for lung cancer, where the telomerase reverse transcriptase (TERT) and cleft lip and palate transmembrane 1-like (CLPTM1L) genes are located (Kang et al, 2008;McKay et al, 2008;Wang et al, 2008;Jin et al, 2009;Rafnar et al, 2009;Zienolddiny et al, 2009;Hsiung et al, 2010).…”
Section: Introductionmentioning
confidence: 99%